The role of the Egyptian drama of Ramadan values ​​and behavior among female university students In the capital Baghdad - hameed, Iman abdulrhman (Journal of Humanities & Social Sciences, 2020)
The aim of the research is to find out the impact of the Egyptian soap operas presented in Ramadan on the behavior of female university students and the sequence of values ​​they possess. What are the Egyptian drama types that are given to them on the grounds that television conveys the exaggerated reality، as some thinkers put it? Leads to the loss of social life from the prevailing traditions and the fall of old customs and excesses of tradition or the establishment of prevailing values ​​and focus on themThe research is a study of the surveys that are interested in studying current or still occurring phenomena where the researcher examines the phenomenon in the place or environment in which it is present، and then collects and scans all the information about that problem or phenomenon،To achieve the goal of the research، the researcher distributed 120 form 60 form for female students of the Faculty of Education Girls and 60 form for students of the Faculty of Science Girls for the questionnaire form either the questionnaire was distributed as a second step on 102 students of them and the difference in the number was the result of absence of a number of students and neglect the form of another number for lack of scientific validity Use of frequencies and percentages and calculation of the value of the arithmetic mean and the test of the following:1- Egyptian soap operas contribute to shaping public attitudes about values ​​and problems in society2- Behavioral patterns of students are linked to what is promoted during the Egyptian series And the importance of research from being discussing the problem began to Iraqi families suffer from it is a change in the behavior of young people، especially girls because of their exposure to drama and serials in general and the Egyptian series in particularThe main results of the research were as follows:1- lying is the most influential behavior by 16.6%، which makes these serials a real danger to the behavior of the Iraqi student، especially the behavior of expatriate and strange from the Iraqi society• The perception of the values ​​of the society negatively affected their exposure to the Egyptian series by 51% and their views changed to equality and justice in the Arab countries by 27.5%3- It turns out that (65%) of the respondents see that the content of the Egyptian serials does not agree with the nature of the Iraqi society due to the prevailing customs، traditions، customs and behavior، especially dress، dress، forbidden drinking and forbidden relations، despite their admiration for these series4- The most important reasons viewers watch the Egyptian series are getting used to watching them during the month of Ramadan، especially since most of the satellite channels show these serials to the Egyptian production in comparison with the rest of the Arab countries on the one hand and the weakness of the Iraqi drama and the other. On the other hand، the researcher sees the importance of the attention of television production institutions in Iraqi drama in terms of the selection of subjects، writing the script and the distinctive directing vision so that it can compete with the Arab drama especially the Egyptian drama.
Keywords: serials; behavior; values